2007
DOI: 10.1016/j.eurpsy.2007.01.1085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and behavioral correlates of enuresis in preschool children

Abstract: checklist , Beck depression inventory and the Scale for evaluation of bullying behaviour in their schools. Their parents also completed Overt agression checklist and Beck depression inventory. Results: Adolescents who presented themselves as bullies in school had more agression in their families than those adolescents who were not involved in school violence. Also adolescents whose parents had high scores on the Beck depression inventory and had autodestructive impulses had statistically higher scores on the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In 43 samples from 40 studies (99 603 children), the effect size between child screen time and internalizing problems was weak but significant ( r , 0.07; 95% CI, 0.05-0.08) (Figure 3). The funnel plot showed some asymmetry (eFigure 2 in the Supplement), indicating possible publication bias; however, the Egger test result did not suggest that smaller sample sizes had more extreme effect sizes. The Q statistic was significant ( Q , 285.10; P < .001; I 2 , 85.27), and moderator analyses were conducted to explain between-study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 43 samples from 40 studies (99 603 children), the effect size between child screen time and internalizing problems was weak but significant ( r , 0.07; 95% CI, 0.05-0.08) (Figure 3). The funnel plot showed some asymmetry (eFigure 2 in the Supplement), indicating possible publication bias; however, the Egger test result did not suggest that smaller sample sizes had more extreme effect sizes. The Q statistic was significant ( Q , 285.10; P < .001; I 2 , 85.27), and moderator analyses were conducted to explain between-study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 95%
“…In the 90 samples from 80 studies (124 027 children), the correlation was small but significant ( r , 0.11; 95% CI, 0.10-0.12) (Figure 2). The Egger test result provided evidence that studies with smaller sample sizes had more extreme effect sizes, and the funnel plot showed asymmetry (eFigure 1 in the Supplement), indicating possible publication bias and/or small-study effects. There was evidence of significant between-study heterogeneity ( Q , 729.78; P < .001; I 2 = 87.80); therefore, moderators were explored (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Screen time may be passive, such as watching a television program, or it can be interactive, such as playing video games or through emerging technologies of virtual reality. Screen media overuse is associated with negative physical and mental health effects among youth including obesity (Institute of Medicine (US) Committee on Prevention of Obesity in Children and Youth, 2005;Zimmerman & Shimoga, 2014), disordered sleep (Dwork M, et al, 2007;Hysing et al, 2015;Zimmerman, 2008), aggressive behaviors (Wilson et al, 2002), attentiondeficit/hyperactivity disorder (Acevedo-Polakovich et al, 2006), impaired cognitive development (Zimmerman & Christakis, 2005), mood disorders (Erdogan et al, 2006), and psychological distress (Erdogan et al, 2006;Hamer et al, 2009;Primack et al, 2009). There is also emerging research of possible benefits for the use of interactive media for children in certain settings (Christakis et al, 2013;Kirkorian et al, 2016).…”
mentioning
confidence: 99%